Management of Injury to the Common Bile Duct in a Patient with Roux-en-Y Gastric Bypass - Sheraz Yaqub; Tom Mala; Øystein Mathisen; Bjørn Edwin; Bjarte Fosby; Dag Tallak Kjærsdalen Berntzen; Andreas Abildgaard; Knut Jørgen Labori (Case Reports in Surgery)
Introduction. Most surgeons prefer Roux-en-Y hepaticojejunostomy (RYHJ) for biliary reconstruction following a common bile duct (CBD) injury. However, in patients with a Roux-en-Y gastric bypass (RYGB) a RYHJ may be technically challenging and can interfere with bowel physiology induced by RYGB. The use of a hepaticoduodenostomy (HD) resolves both these issues. Presentation of Case. We present a case of CBD injury during laparoscopic cholecystectomy one year after laparoscopic RYGB for morbid obesity. Due to adhesions and previous surgery with RYGB, we did not want to interfere with the RYGB physiology by anastomosing the CBD to the jejunum or ileum. Succeeding a full Kocher’s maneuver we performed biliary reconstruction by a tension-free end-to-side HD. The postoperative recovery was uneventful and the patient was discharged after eight days. At four-month follow-up, the patient had stable weight and normal laboratory test results. MRCP demonstrated normal intra- and extrahepatic bile ducts with status after HD. Discussion. We propose that HD should be considered in treatment of CBD injury in post-RYGB patients as it may reduce the risk of interfering with the post-RYGB physiology.